Problematika Pernikahan Beda Agama dalam Pandangan Fiqh dan UU Perkawinan di Indonesia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
Interfaith marriage is a complex issue and often becomes a subject of debate in Indonesian society. In both legal and religious contexts, this type of marriage faces various challenges, particularly from the perspective of Islamic jurisprudence (fiqh) and the Indonesian Marriage Law. This journal aims to analyze the problems surrounding interfaith marriage in Indonesia by examining Islamic legal views, regulatory frameworks, and the resulting social implications. From the fiqh perspective, the majority of scholars agree that a Muslim woman is not permitted to marry a non-Muslim man, whereas the marriage of a Muslim man to a woman from the People of the Book (Ahl al-Kitab) remains a topic of debate, depending on social context and public interest (maslahah). This reflects how Islamic law prioritizes the stability of faith (aqidah), household leadership, and the continuation of religious values in the upbringing of children. From the standpoint of national law, Indonesia’s Marriage Law No. 1 of 1974 places the validity of a marriage under the religious laws of the respective parties, making it difficult for interfaith marriages to be officially registered. As a result, such couples often face administrative barriers, issues in inheritance law, child custody rights, and social discrimination. This study concludes that a fair and constructive approach is necessary in addressing this issue, while preserving religious principles and maintaining social harmony in Indonesian society.